Metabolic Alterations in FMR1 Premutation Carriers - Cao, Yiqu; Peng, Yun; Kong, Ha Eun; Allen, Emily G.; Jin, Peng (Frontiers in Molecular Biosciences, 2020)
FMR1 gene premutation carriers are at risk of developing Fragile X-associated tremor/ataxia syndrome (FXTAS) and Fragile X-associated primary ovarian insufficiency (FXPOI) in adulthood. Currently the development of biomarkers and effective treatments in FMR1 premutations is still in its infancy. Recent metabolic studies have shown novel findings in asymptomatic FMR1 premutation carriers and FXTAS, which provide promising insight through identification of potential biomarkers and therapeutic pathways. Here we review the latest advancements of the metabolic alterations found in asymptomatic FMR1 premutation carriers and FXTAS, along with our perspective for future studies in this emerging field.